Predictors influencing dental clinic utilization in primary health care: A retrospective analysis of 233,069 patient records in Riyadh, Saudi Arabia - Faris Fatani; Ashraf El-Metwally; Lubna Alkadi; Hanan M Al Kadri; Nouf Binhowaimel; Abdulrahman Almuflih; Badr F Al Khateeb; Awad Alshahrani; Afrah Alsaif; Aljohrah Aldubikhi (Saudi Dental Journal)
Aim: This study aims to identify and address the predictors that promote or prevent the utilization of dental services in primary health care (PHC) centers located in Riyadh, Saudi Arabia, with an ultimate goal to increase the uptake of oral health care (OHC) services. Methodology: Registration data from 99 PHC centers was used. For each patient visiting a PHC center, information on the number of dental visits was captured. Continuous data was summarized as means, medians, and ranges, and categorical data as frequencies (%). The strength of association was reported as an incidence rate ratio (IRR) with 95% confidence interval (CI) and a p-value. Further analysis was conducted to illustrate the association between dental care visits and factors found independently significant in the final multivariate model using Karl Pearson correlation coefficient and t-test. All tests were two-sided and a p-value of p < 0.05 was considered significant. Results: The comorbidity profile of patients shows that 11,751(5%) were diabetic, while hypertension amounted to 10,712(4.6%). A statistically significant inverse correlation was observed between dental care visits and both age (r = −0.025, p < 0.001) and BMI (r = −0.013, p < 0.001). Mean dental care visits were significantly higher in patients without hypertension compared with those with hypertension (p < 0.001). Moreover, there was an approximate 4% increase in dental care visits among females compared to males, although this difference was not statistically significant. Conclusion: The study identified three predictors contributing to the low utilization of dental services in PHC centers in Riyadh. These include an inverse association between both age and body mass index (BMI) and the utilization of OHC. Additionally, the mean dental care visits were significantly higher for patients without hypertension in comparison to hypertensive patients.